48.3k views
4 votes
If f(x) = 3x-2 and g(x)= x^2 +1, find (f+g)(x).

If f(x) = 3x-2 and g(x)= x^2 +1, find (f+g)(x).-example-1
User Yashawant
by
6.0k points

2 Answers

1 vote

Answer:

It's choice D.

Explanation:

(f + g)(x) = f(x) + g(x)

= 3x - 2 + x^2 + 1

= x^2 + 3x - 1.

User Mikolajbe
by
5.8k points
1 vote

Answer:

D. x^2+3x-1

Explanation:

You have:

f(x) = 3x-2

g(x)= x^2 +1

Then:

(f+g)(x)=f(x)+g(x)

(f+g)(x)=(3x-2)+(x^2+1)

(f+g)(x)=3x-1+x^2 (-2+1=-1)

(f+g)(x)=x^2+3x-1 (ordering terms)

User Try Maadee
by
6.3k points